POTRET SOSIAL KEBERAGAMAAN YANG HARMONIS DI PUJA MANDALA, NUSA DUA BALI - Fathor Rahman (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
This paper unravels a social portrait of harmonious living between religious groups in Puja Mandala, Nusa Dua Bali. Having been known to reside four religious shrines since 1994, Puja Mandala communities passed down the legacy of religious tolerance based on three pillars; co-existence, diversity, and tolerance. This paper elaborates various factors that made those three pillars possible to co-exist condusively among majorities with influential hindu traditions. By stating the following problems of how does Puja Mandala build harmonious living between religious groups, what is the social portrait of that harmonious living, and how do religious groups adopt that harmonious living into their social interaction, this paper uncovers the contributing factors and supports from various authorities that shape the stereotype of Puja Mandala as a miniature of harmonious living the citizens of Bali are proud of. Religious authorities, religious shrine officials, and interreligious congregations are mutually contributing to build the image of harmonious living in diversity at Puja Mandala as we know today.